Evaluation of the effect of ozonated water in treatment of denture stomatitis associated with removable prosthetics - Basma Mostafa; Asmaa Nabil Elboraey; Hossam M. El-Masry; Wessam M. Dehis (Bulletin of the National Research Centre, 2024)
Abstract Background Ozone therapy is highly demarcated in the dental field owing to its efficient antimicrobial action in its gaseous and aqueous forms. One of the most common difficulties accompanied by utilizing dentures is denture stomatitis (DS) which is principally triggered by Candida albicans (C. albicans). Objectives Assessing and comparing the impact of ozonated water versus chlorhexidine mouthwash on healing of intra-oral inflammations associated with complete dentures. Subjects and methods Fifty middle-aged male completely edentulous patients wearing complete dentures were screened for the possibility of having any accompanied DS and/or C. albicans. Patients were randomly distributed into two groups. Group I patients were treated with chlorhexidine mouthwash and oral hygiene measures (OHM); while, Group II patients received ozonated water as a mouthwash and OHM. Evaluation of inflammation, pain grade, and oral Candidiasis count took place for all patients in all visits; from the initial day of treatment and after 7, 14, and 30 days. Results The inflammation’s area and severity together with pain grade showed a significant decrease with time when using both chlorhexidine mouthwash and ozonated water. Comparing the use of chlorhexidine mouthwash and ozonated water together showed insignificant differences. Regarding the Candida forming units (CFU) there was a significant decrease in the colonies number over time, but with insignificant difference between the two groups. Conclusions Ozonated water showed favorable results in reducing the area and severity of inflammation and pain grade. Ozonated water has an antifungal effect and can be used as an alternative mouth rinse in treating denture stomatitis.